Dietary choices and greenhouse gas emissions - assessment of impact of vegetarian and organic options at national scale - Risku-Norja, Helmi; Kurppa, Sirpa; Helenius, Juha (Inderscience Enterprises, 2009)
This study quantifies the sources of agricultural GHG emissions and explores the impact of diet on GHG emissions in Finland. The emissions associated with production of basic food items were quantified for four diet options. For current average food consumption, emissions from soil represent 62% of the total. The emissions due to enteric fermentation contribute 24%, and energy consumption and fertiliser manufacture both about 8%. Regarding GHG emissions, environmental performance of the extensive organic production is poor. A strict vegan diet would nearly halve the agricultural GHG emissions, but reduction of the total emissions would be about 8%. Reducing the GHG emissions through food consumption would require large-scale changes among the entire population. Instead of stressing the impact of individual citizens' diet choices, more attention should be paid to social learning. Attention should be paid to the overall sustainability of food supply, not only to the GHG emissions.
Keywords: Ma; Re; Ys; elintarvikkeet; kulutus; ruoka; ruoankulutus; kasvisruokavaliot; päästöt; ilmastonmuutokset; tavanomainen viljely; luonnonmukainen viljely; ympäristövaikutukset; food consumption; per capita per annum; vegan and non-ruminant diet; kasvihuonekaasut